Does gender diversity promote non-conformity? - Makan Amini; Mathias Ekström; Tore Ellingsen; Magnus Johannesson; Fredrik Strömsten (Research Institute of Industrial Economics (IFN), 2015)
Failure to express minority views may distort the behavior of company boards, committees, juries, and other decision-making bodies. Devising a new experimental procedure to measure such conformity in a judgment task, we compare the degree of conformity in groups with varying gender composition. Overall, our experiments offer little evidence that gender composition affects expression of minority views. A robust finding is that a subject's lack of ability predicts both a true propensity to accept others' judgment (informational social influence) and a propensity to agree despite private doubt (normative social influence). Thus, as an antidote to conformity in our experiments, high individual ability seems more effective than group diversity.
Keywords: C90; D02; D71; D83; J16; 330; Conformity; Gender Differences; Group Composition; Skill